PENILAIAN KINERJA INVESTASI TI APLIKASI SISTEM INFORMASI MAHASISWA BARU PADA UNIVERSITAS XYZ: ASSESSMENT OF IT INVESTMENT PERFORMANCE OF NEW STUDENT INFORMATION SYSTEM APPLICATIONS AT XYZ UNIVERSITY - Dhya Aminaturrahmah; Astrid Dyssa Rachmawati; Renny Sari Dewi (Jurnal Teknologi dan Terapan Bisnis, 2021)
Maturity level assessment is considered very important in the information technology sector, one of which is in the field of education. It includes not only academic activities in the classroom, but also non-academic activities such as organization and committee. During pandemic condition, all activities on campus are required to be completely online, including the orientation period for new students as an annual routine. XYZ University is one of the educational institutions that also implements an online orientation period. Not only meeting with the video conference application as a media, which are members of the committee also create a web-based application where the application contains all information related to orientation period activities, including materials, values, and information about the campus activities which must be shared digital in this situation. The application previously described must be calculated for its maturity level to find out whether it has provided maximum benefits or vice versa for the university as the party that should provide funds and looking for parties from outside the university. To answer this problem, it is necessary to measure IT performance using VAL IT 2.0 which can provide a conclusion of the benefits.